'Releasing the Chaos of Energies': Communicating the Concurrences in Trevor Joyce's Appropriative Poems. Issue 1 (May 2016) - O'Mahony, Niamh
Abstract : This essay addresses appropriation in the poetry of Trevor Joyce. The author analyses the function and impact of textual borrowing in a number of recent poems by Joyce, comparing and contrasting Joyce's appropriative practice to that of a number of contemporary poets.